ACMEOLOGICAL COMPETENCE OF FUTURE SOCIAL EDUCATORS: CURRENT STATE - Ilyassova, lira; SHOLPANKULOVA, G.; KOSMAGANBETOVA, G. (Pedagogy and Psychology, 2024)
Acmeological competence is an important issue for future social educators. This competence contributes to developing their skills to implement their professional activities, adjusting to changing circumstances, and being adaptable in professional endeavors in a rapidly changing world. This paper explores the current situation of future social educators’ acmeological competence. The aim of this research is to define the current state of acmeological competence of future social educators and give recommendations to improve the situation. To collect the data a survey related to social educators’ acmeological competence has been employed. The conducted survey revealed that approximately half of the future social educators are unfamiliar with the term. However, despite their unfamiliarity with “acmeology”, they understand the importance of professional development. The authors of the research believe that incorporating acmeological competence components into the social education curricula and developing initiatives aimed at enhancing acmeological competence will increase future social educators’ acmeological awareness and skills.